Mapping Of Batang Merao River Water Quality Using A Geographic Information System (GIS) In Kerinci Regency - Zaitun Almunawarah; Erna Juita; Irwan Irwan (Jurnal Ilmu Sosial dan Humaniora, 2025)
The Batang Merao River is one of the main water resources utilized by the people of Kerinci Regency to meet various needs, such as bathing, washing, irrigation, and other household activities. The increasing community activities along the riverbanks have the potential to cause a decline in water quality due to the entry of domestic waste into the river body. This study aims to map the water quality of the Batang Merao River using a Geographic Information System (GIS) so that the spatial distribution pattern of water quality conditions can be identified. The study used a quantitative descriptive method with sampling in the upstream and downstream parts of the Batang Merao River. Water quality data were obtained through laboratory testing of water quality parameters, then processed using a Geographic Information System through the process of inputting coordinates, spatial interpolation, and preparing thematic water quality maps. The mapping results show that water quality conditions have changed from upstream to downstream. The upstream area still shows relatively better water quality compared to the downstream area which is influenced by the increasing household activities along the riverbanks. Mapping using GIS is able to describe the spatial distribution of water quality more clearly so that it can be used as a basis for decision making for the management and control of pollution in the Batang Merao River